Reducing EMI by Multiple Slits Shielding - Arik, Eray; Tabakcıoğlu, Mehmet Barış (Ieee, 2017)
Electromagnetic compatibility (EMC) is vital for health and more reliable electric and electronics systems. All electronic devices have to provide EMC tests. In order to increase the quality of service of all electronic devices, a shielding mechanism has to be provided in order to eliminate electromagnetic interference (EMI). In this study a multi-slits shielding mechanism is proposed by using Uniform Theory of Diffraction and geometrical optic models. Multi-slits structure does not permit passing the direct field much and provide dominant field contribution from diffracted field. Due to using diffracted field instead of direct field, EMI is reduced.
9th International Conference on Electronics, Computers and Artificial Intelligence (ECAI) -- JUN 29-JUL 01, 2017 -- Targoviste, ROMANIA
Keywords: EMC; EMI; UTD; Shielding; High frequency techniques